Implementasi Pembacaan Asmaul Husna Dalam Membentuk Karakter Islami Pada Siswa MTs Al-Azhar Menganti Gresik - Moh. Khoirul Anam; Abdul Halim (Jurnal Pendidikan Agama Islam Miazhar, 2023)
There are many deviations and actions that should not be done in the world of education. In Islamic education, religious character education has an important role in preventing acts that deviate from Islamic teachings. One of the first steps to create a nation with an Islamic perspective is through Asmaul Husna. MTs Al Azhar makes Asmaul Husna a habit that is carried out routinely before studying, to form Islamic character in students. Through habituation, it makes students accustomed to doing good things and students can practice the meaning of Asmaul Husna in everyday life. The aims of this thesis research are: 1) to describe the implementation of reading Asmaul Husna in forming Islamic character in students, 2) to describe the supporting and inhibiting factors of reading Asmaul Husna in forming Islamic character in MTs Al Azhar Menganti Gresik students. This study used a qualitative approach with a descriptive research type. Determination of research subjects using purposive. Data collection techniques through observation, interviews, and documentation. Data analysis using data reduction, data presentation, and conclusions. The validity of the data uses triangulation, namely source triangulation and technique triangulation. The results of this thesis research are: first, the reading of Asmaul Husna is carried out every morning before the KBM starts. Second, the supporting factors in forming Islamic character in students are student interest, the active role of the teacher, and adequate facilities. While the inhibiting factors, namely the lack of student discipline, lack of student awareness, the loss of the Asmaul Husna pronunciation sheet, the absence or delay of the accompanying teacher, and the delay in reading from the center. To deal with these obstacles there must be self-awareness, both from students, teachers and parents, besides that there must be more assertiveness in implementing school rules.